Harari's geschiedenis van de toekomst: Een techniekfilosofisch commentaar - Munnik, René (Tijdschrift voor theologie, 2019)
Homo Deus is an extensive critique of the ‘humanist doctrine’ which, according to Harari, entails that humanity considers itself to be the source of all meaning and authority. Nowadays, he believes, this ‘humanist faith’, combined with science and technology, would lead to nothing short of a pursuit of immortality, happiness and divinity, by replacing humanity with algorithms (‘dataism’). But in doing so, humanism does not just hasten its own downfall, it may also hasten the end of humanity and maybe even that of the planet. Harari’s anti-humanist critique of ‘dataism’ does bespeak two ambivalences, however. The first concerns his perspective on humanism: Harari criticises humanism from a humanist concern. The second concerns his attitude towards science and technology: in his approach, technical sciences are both the debunkers of the illusions of humanism and the tool for the realisation of its illusory goals. Harari relies upon a technology he mistrusts. Both these ambivalences are, as I will show, part of the current scientific and technological framework in which fundamental shifts are taking place that also concern the foundations of Christianity and humanism. Homo Deus seems to be a symptom rather than a critical reflection of these shifts. I demonstrate this by pointing out two relevant aspects: First the uncertainties involved in the social embedding of new technologies: 1. the actual uncertainty as to the social consequences, 2. the normative uncertainty with regard to the influence of technology on the criteria by which those consequences will be judged in the future, and 3. the symbolic uncertainty which renders any instrumentalist division of roles between (autonomous) humanity/designer/user and (heteronomous) technology/design/means impossible, right from the start. In my elaboration of the latter, I point out the second aspect: the tremendous role of ‘technological mediation’, both in the genesis of and the threat to the Christian and humanist ideas of humanity and world. A textbook example of this mediation is the influence of alphabetic script, a technology, has had on religions (of the book), scholarly thought (philosophy) and the notion of ‘history’. This leads us to the conclusion that we cannot be flippant with regard to any technology that influences the status of the letter in culture and society, as it appears to be constitutive to both the Christian and humanist self-image. Although Harari does not entirely fail to appreciate this, he does underestimate its importance.